Predicting the rate of invasion of the agent of Lyme disease Borrelia burgdorferi. Issue 2 (4th February 2013) - Ogden, Nicholas H.; Lindsay, L. Robbin; Leighton, Patrick A.; Sheppard, Andy
Ixodes scapularis